A Review on Green Synthesis of Copper Nanoparticles Using Plant Extracts: Methods, Characterization, and Applications - Tripathy, Sweta Kumari; Kumar, Satendra; Kaushik, Niranjan (Pharmaceutical Nanotechnology, 2025)
<span class=
Keywords: Green synthesis